In Silico Potential Analysis of Acorus calamus as a Mental Depression Therapy - Damayanti, Fitria Dwi; Jamil, Ahmad Shobrun; Rofida, Siti; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2473, 2023)
Depression is a common but serious mood disorder. This disease causes severe symptoms that affect one's emotions, thoughts, and daily activities, such as sleep, eating, or working. According to the National Youth Mental Health Survey of Indonesia, in 2022, 15.5 million (34.9%) teenagers suffer from mental disorders and 2.45 million (5.5%) have mental illnesses. Acorus calamus is believed to have antispasmodic, carminative, antihelmintic, aromatic, expectorant, nausea, soothing, sedative, and stimulant properties. It is also used to treat epilepsy and mental illness, chronic diarrhea, dysentery, and stomach pain.  This study aims to determine the molecular mechanisms of the bioactive compound antidepressant Acorus calamus using pharmacological tissue analysis. Acorus calamus compound data obtained from Dr. Duke's database, screening of the absorption, distribution, metabolism, and excretion (ADME) of Acorus calamus Compounds with SwissADME, prediction of the Acorus calamus target compounds protein with SwissTargetpPrediction, analysis of the pharmacological network with String-DB and its visualization with Cytoscape version 3.10.1. Searching for the contents of Acorus calamus compounds resulted in 69 components and found 12 compounds that have ADME criteria that match the drug compounds (Drug Likeness/DL). The pathways correlated with therapy are the neurotransmitters of serotonin. The known target proteins are MAOA, ESR1, GRM5, CRHR1, HTR2A, DRD2, SLC6A4 and CHR with compounds that correlate with mental depression therapy, among others Aceteugenol, Acoradin, Acoramone, Alpha-Asarone, Beta-Asarone, Calamenone, Camelone, Elemicin, Isoacorone, Sekishone, trans-Isoelemicine, Epoxyisoacoragermacrone.